Exploring the Opportunities for Women-owned SMEs in Cambodia - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
Facilitating a dynamic and competitive small-and medium-sized enterprises (SME) sector is a strong priority in both developed and emerging economies. In this context, despite significant success in sustaining high economic growth and job creation, Cambodia is at a relatively early phase of developing targeted SME policies. SMEs, both men- and women-owned, face several challenges, including access to markets, low productivity, lack of qualified and skilled labor, lack of innovation, as well as a complicated and relatively costly registration procedure. This study intends to capture data on both men- and women-owned SMEs in Cambodia to be able to better understand the gender implications in the provision of targeted business development as well as banking services in the country. The objective of the research is thus to inform the government, private and state-owned banks as well as the international community about the financial and non-financial constraints faced in particular by women-owned SMEs that can be addressed at policy, financial sector, and market levels. In addition, the study aims to outline the opportunities that women-owned SMEs represent for banks and how banks are missing out on a separate and strategic customer segment. It also explores potential solutions that can be utilized to help overcome the typical barriers faced by women.